Development of methods for objectively quantifying performance of active suspension systems - Arvidsson, Kristofer; Runólfsson, Róbert Már (My University, 2019)
Ride is one of the attributes of vital importance in modern passenger vehicles. This is closely connected to the suspension system of the vehicle, which often consists of passive springs and dampers. For these passive systems there are methods and metrics to evaluate their performance but for semi- and fully active suspension systems there are not well-defined methods and metrics. The objective of this thesis is therefore to develop a method to objectively quantify the performance of semiand fully active suspension systems. The goal is to answer the question: "What is a good semi-active or fully active suspension system?". The evaluation of the suspension systems is done in three ways; using simulations in IPG CarMaker, objective testing of physical cars and through subjective assessments of the same cars. The results are then processed using MATLAB to find any desired metrics. Here a correlation study is also carried out to see what objective measurements correlate best to the subjective scores. From the results, it is evident that the road used for small amplitude primary ride and flat surface secondary ride in simulations does not produce results comparable to the physical tests. For the large amplitude road some correlations are found, for instance between the objective heave movement and subjective comfort rating. For secondary ride on rough surface the objective pitch RMS correlates to subjective choppiness rating. These results are not certain as the standard deviation in them is significant and data for more cars and drivers would be required to increase certainty. However, this shows that it is possible to find objective metrics to describe the performance of a suspension system, including active ones, and thereby estimate a subjective rating from a value of the objective metric. To conclude; the method proved functional in the sense that it helps translate subjective assessments of a vehicle’s ride quality with semi- and fully active suspension into objective, quantifiable metrics. While having testing procedures stricter and defined in greater detail could have produced stronger correlations, as well as having larger data sets in the form of number of test cars, test drivers and procedures, it can still be considered a proof of concept. Moreover, it forms a good basis and a useful tool for further work in creating a fully effective ride evaluation method.
Keywords: Transport; Fastkroppsmekanik; Farkostteknik; Transport; Solid mechanics; Vehicle Engineering